2022
DOI: 10.1002/eap.2699
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of farmland bees across rural–urban landscapes in a tropical megacity

Abstract: Urbanization poses a major threat to biodiversity and food security, as expanding cities, especially in the Global South, increasingly compete with natural and agricultural lands. However, the impact of urban expansion on agricultural biodiversity in tropical regions is overlooked. Here we assess how urbanization affects the functional response of farmland bees, the most important pollinators for crop production. We sampled bees across three seasons in 36 conventional vegetable‐producing farms spread along an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Additionally, pollinators require diverse nesting habitats, which can be scarce in urbanized landscapes. For instance, Marcacci et al, (2022) found that A. florea, the main mango pollinator in our study, declined with urbanization because of the lack of suitable nesting sites such as hedges and bushy vegetation. We thus encourage the creation of patches of native wild flowering plants as well as the preservation of seminatural vegetation within mango farms to provide floral resources and nesting sites, which will eventually benefit pollinators and mango pollination.…”
Section: Management Recommendationsmentioning
confidence: 65%
See 3 more Smart Citations
“…Additionally, pollinators require diverse nesting habitats, which can be scarce in urbanized landscapes. For instance, Marcacci et al, (2022) found that A. florea, the main mango pollinator in our study, declined with urbanization because of the lack of suitable nesting sites such as hedges and bushy vegetation. We thus encourage the creation of patches of native wild flowering plants as well as the preservation of seminatural vegetation within mango farms to provide floral resources and nesting sites, which will eventually benefit pollinators and mango pollination.…”
Section: Management Recommendationsmentioning
confidence: 65%
“…We then calculated the proportion of grey area within a 2000 m radius around the centroid of each mango farm. A radius of 2000 m was found to be the best spatial scale to explain the abundance of pollinators in our study region (Marcacci et al, 2022).…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…A pixel-wise image classification was done using a deep learning model, that is a multilayer perceptron network (Marcacci et al, 2021). We then calculated the proportion of grey area in the study sites' surroundings within a 500 m radius, corresponding to the spatial scale at which most bee species experience the landscape in our study region (Marcacci, Grass, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%